Ethnic persistence and change in Europe and America: traces in landscape and society - Frantz, Klaus; Sauder, Robert A. (Veröffentlichungen der Universität Innsbruck, 1996)
"This book is an excellent resource for the study of ethnicity as a central topic in the geography of North America and Europe, providing an important reexamination of culture as a part of such research."